Carbonate Solvents and Ionic Liquid Mixtures as an Electrolyte to Improve Cell Safety in Sodium-Ion Batteries - T. D. Vo; H. V. Nguyen; Q. D. Nguyen; Q. Phung; V. M. Tran; P. L. M. Le (Journal of Chemistry)
Ionic liquid-based electrolytes proved to be effective in terms of alleviating the safety problems associated with lithium/sodium ion batteries, especially for large-scale applications, due to their superior thermal stability and nonflammability. The main disadvantage of ionic liquids is their relatively high viscosity. Adding a suitable amount of organic “thinning” solvents could be a potential solution for this problem: while the electrolyte viscosity is greatly reduced, the electrochemical properties and thermal stability remain almost as good as those of pure ionic liquid. In this study, electrolyte mixtures based on 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl) (EMI-TFSI) and carbonate solvents (EC-PC) were prepared. The electrochemical compatibility in half-cell configuration with respect to sodium metal anode of various electrode materials, including SnS/C, hard carbon (HC), and Na0.44MnO2, was evaluated. Moreover, the thermal stability, the flammability, and the conduction mechanism of such electrolyte mixtures were also explored and discussed.